2001
DOI: 10.1037/0894-4105.15.2.199
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of attention rehabilitation after an acquired brain injury: A meta-analysis.

Abstract: The efficacy of attention rehabilitation after an acquired brain injury was examined metaanalytically. Thirty studies with a total of 359 participants met the authors' selection criteria. Studies were categorized according to whether training efficacy was evaluated by comparing pre-and posttraining scores only or included a control condition as well. Performance improved significantly (using the d + statistic) after training in pre-post only studies but not in pre-post with control studies. Further analyses sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
87
0
11

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(103 citation statements)
references
References 71 publications
5
87
0
11
Order By: Relevance
“…Cognitive rehabilitation typically involves one of these two basic strategies (Park & Ingles, 2001). The first approach attempts to retrain directly those cognitive processes that have been impaired by injury based on the notion that damaged neural circuits can be retrained if they have been partially or substantially spared after injury (Robertson & Murre, 1999).…”
mentioning
confidence: 99%
“…Cognitive rehabilitation typically involves one of these two basic strategies (Park & Ingles, 2001). The first approach attempts to retrain directly those cognitive processes that have been impaired by injury based on the notion that damaged neural circuits can be retrained if they have been partially or substantially spared after injury (Robertson & Murre, 1999).…”
mentioning
confidence: 99%
“…Deficits in working memory (WM) and executive attention are common problems after acquired brain injury [1][2][3][4]. WM is the ability to hold and manipulate information during a short delay, and to be able to make a response based on that internal representation.…”
Section: Introductionmentioning
confidence: 99%
“…25 APT is a theoretically based, hierarchical, multilevel treatment, including sustained, selective, alternating, and divided attention 25 typically administered by neuropsychologists, occupational therapists, speech language therapists, and other rehabilitation specialists, as is appropriate within their scope of practice. APT has been examined in small, nonrandomized evaluations in TBI samples [25][26][27][28][29]34 and is the basis of rehabilitation packages for mild deficits (APT-II) 30 and for children treated with radiation after cancer. [31][32][33] In a meta-analysis of TBI studies (total nϭ359) Park and Ingles 34 found attention improved significantly after specific skills training in prepost studies.…”
mentioning
confidence: 99%